48 - SELECTED TIME SPACE CHARACTERISTICS IN FEMALE POLE VAULT (Fiep Bulletin - online, 2023)
This research is stressed at time and space characteristics (centre of gravity movements) in female pole vault. Kinetic parameters were gained by two-dimension analyser Consport Motion Analysis System (CMAS). There are involved 19 female pole vault jumpers with sport performance 380 – 483 cm, divided on 2 different groups; higher and lower level from the point of sport performance.We found that in time parameters reached better results high performance level jumpers in phases hanging and lifting. It is coursed by better transmission on pole after take-off and by better work on the pole. As for the centre of gravity the jumpers of higher performance reached higher growth in all phases. The most significant difference can be seen in phase of lifting. Comparison of time and space characteristics enable to show the way for technique improvement in female pole-vault.
Keywords: female pole vault; rhythm of the jump; centre of gravity height